First-year English Majors’ Use of Autonomous Learning Strategies - Tham, Duong My (VNU Journal of Science: Education Research; Vol 36 No 3DO - 10.25073/2588-1159/vnuer.4439, 2020)
This study aimed at investigating the frequency of autonomous learning strategies used by 173 English majors at a Ho Chi Minh City-based university. The quantitative data collected from the closed-ended questionnaire were statistically analyzed by means of SPSS 20. The results showed that there were insignificant differences in terms of frequency among three groups, namely cognitive, metacognitive, and resourse management strategies. Statistically, the resource management strategies group achieved the highest mean score (M=3.31; SD=0.59), followed by the cognitive strategies (M=3.29; SD=0.71) and the metacognitive strategies (M=3.27; SD=0.60). Turning to the details, however, the use of strategies in each group varied in degree. As for the resource management strategies, in particular, the strategies concerning learning environment management, internet-based indendendent learning, and peer learning were preferred to the strategies of teacher support and time management, whereas the participants tended to use more rehearsal and elaboration strategies than organization ones in the cognitive strategies and more critical thinking and monitoring strategies than goal setting ones in the metacognitive strategies.